2015
DOI: 10.1186/s12957-015-0442-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast adenoid cystic carcinoma in a 19-year-old man: a case report and review of the literature

Abstract: Adenoid cystic carcinoma (ACC) of the breast is very rare in males. There have been only eight previous articles published on breast ACC in males. Here, we will report on the first case of this type of tumor in the Chinese province of Hainan. The patient was a 19-year-old male, and he underwent a radical mastectomy (RM) with axillary lymph node dissection. The histopathological examination specimen revealed that surgical margins were negative; none of the 41 axillary lymph nodes excised were positive for malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…Generally, they occur in female patients with a median age of 58 to 64 years. Therefore, there are limited guidelines for treatment and diagnosis, and they are based on guidelines used for ACC of the breast in females (1)(2)(3)(4)(5)(6). In the present study, we reported a rare case of ACC of the breast in a 42 year-old man.…”
Section: Introductionmentioning
confidence: 73%
“…Generally, they occur in female patients with a median age of 58 to 64 years. Therefore, there are limited guidelines for treatment and diagnosis, and they are based on guidelines used for ACC of the breast in females (1)(2)(3)(4)(5)(6). In the present study, we reported a rare case of ACC of the breast in a 42 year-old man.…”
Section: Introductionmentioning
confidence: 73%
“…Few cases of male AdCC have been reported, thus its causes and clinical pathological features have not been completely characterized [9][10][11]. The clinical features of published male AdCC cases are summarized in table 1 [12][13][14][15][16][17][18]. Among these, AdCC of the male breast occurs in wide age distribution, which ranges from 13 to 82 years.…”
Section: Discussionmentioning
confidence: 99%
“…Blacks were 39 percent less likely than whites' morbidity (Ghabach et al, 2010). Most cases are female, but occasionally there are male cases reported (Tang et al, 2015), and domestic literatures report less.…”
Section: Epidemiologymentioning
confidence: 92%